In Vitro Medium-Term Conservation of Several Carnation Accessions through Nutrient Modification - Kurniawan Budiarto; Budi Marwoto; Rudy Soehendi (Buletin Plasma Nutfah, 2013)
Modification of osmotic pressure of in vitro medium-term canbe applied to conserve carnation accessions. This successfulmethod inspired the use of nutrient modification technique tohave the same function as far as these concerned. The researchwas then, conducted to evaluate in vitro media for preservingseveral carnation accessions in low temperature conditions.The research was carried out at Indonesian Ornamental CropsResearch Institute (IOCRI) from January 2007 to March 2008.A randomized completely block design with 25 replicationswas used to accomplish the combination of two factors. Thefirst factor was six commercial carnation accessions, namelycv. Light Pink Candy, Aicardy, Torpedo, Malaga, President,and Rendezvouz. While the second factor dealt with fourformulations of conservation media i.e. ½ MS + DMSO 3% +4% sucrose, modified hyponex + 4% sucrose, modifiedhyponex (no sucrose) and ½ MS + 4% sucrose (control). Theresults showed that medium term in vitro conservation forcarnation were successfully conducted up to 10 months usingin ½ MS + DMSO 3% + 4% sucrose and modified hyponex +4% sucrose without any significant differences and decreasesin viability when transferred in to shoot induction media. In theabsent of sucrose, however, the plantlet survivals were only upto 8 months. No significant variation on viability and numberof survival plantlet was observed among the carnationaccessions in all media tested.